Catalyst‐Switchable Regiocontrol in the Direct Arylation of Remote CH Groups in Pyrazolo[1, 5‐a]pyrimidines1. Issue 30 (10th June 2015) - Bedford, Robin B.; Durrant, Steven J.; Montgomery, Michelle
Abstract The regiodivergent palladium‐catalyzed CH arylation of pyrazolo[1, 5‐a]pyrimidine has been achieved, wherein the switch in regioselectivity between positions C3 and C7 is under complete catalyst control. A phosphine‐containing palladium catalyst promotes the direct arylation at the most acidic position (C7), whereas a phosphine‐free catalyst targets the most electron‐rich position (C3).